Interactive Digital Book Development for Computer and Network Fundamental Teaching Subject based on Four - D Model at Indonesian Computer and Network Engineering Vocational High School - Herlambang, Admaja Dwi; Akhmadi, Lutfiani; Wijoyo, Satrio Hadi (Journal of Information Technology and Computer Science, 2019)
Computer and Network Fundamental is one of the teaching subjects atComputer and Network Engineering Vocational High School in Indonesia. Thelearning activities at the research location was less interactive because of thelearning process still uses conventional textbooks or static digital books.Solutions that offered in the research are not only interactive digital book productdevelopment inappropriate way but also product implementation in experimentaldesign. The development used Four-D Model. The experimental design usedMatching-Only Pretest-Posttest Control Group Design. The instrumentation usedobservation, interviews, questionnaires, and tests. Content Validity Content(CVR) value based on Subject Matter Experts (SMEs) evaluation result for goal,learner, learning, context, and technical criteria are above 0.75. Paired T-Test andIndependent T-Test results showed that interactive digital book implementationin the learning process can cause an enhancement in student learning outcomes.